Eudaimonia Around the Kitchen: A Hermeneutic Approach to Understanding Food Well-Being in Consumers' Lived Experiences. (April 2019) - Mugel, Ophélie; Gurviez, Patricia; Decrop, Alain
This article focuses on food well-being (FWB) in consumers' lived experiences. Adopting a consumer-centric and interpretive approach, the authors combine phenomenological interviews, photo elicitation, and personal diaries to develop a better understanding of FWB. The present research findings lead to a proposed conceptual model of the FWB experience. These elements reflect the eudaimonic approach to well-being, which is related to individual fulfillment and personal growth and helps define FWB not only as a positive relationship with food but also as a eudaimonic experience that includes various processes, meanings, contextual conditions, and resulting moods and emotions. The authors' findings may help consumers, public authorities, and activist networks reinvest meanings and values into individuals' relationship with food.